Blood and Intestine Profile of Broilers Fed Averrhoa bilimbi Fruit, Wheat Bran, and Yeast Blends - A. Pratama; T. Yudiarti; S. Sugiharto; T. Ayaşan (Tropical Animal Science Journal, 2022)
A. bilimbi fruit filtrate, wheat bran, and S. cerevisiae contain bioactive components favorable to broiler health. The use of these compounds in combination was expected to exert synergistic effects on broilers. The study investigated the effect of a combination of A. bilimbi fruit filtrate, wheat bran, and S. cerevisiae on haematological indices and intestinal selected bacteria and morphology of broilers. A total of 280 broiler chicks were randomly divided into 4 groups with 7 replications, including CONT (chicks offered diet without additive), TBLEND1, BLEND2, and BLEND3 (chicks offered diet with 0.25%, 0.5%, and 1% of the additive combination of A. bilimbi fruit filtrate, wheat bran, and S. cerevisiae), respectively. For data collection, the chicks were blood sampled at day 21 and 35, and slaughtered at day 35. The data were statistically treated with analysis of variance according to a completely randomized design. On day 21, the erythrocytes and haemoglobin levels were lower in BLEND2 and BLEND3 than those in CONT and BLEND1 (p<0.05). The leukocytes and lymphocytes values were lower in BLEND2 and BLEND3 than those in CONT (p<0.05). On day 35, erythrocytes were lower (p<0.05) in BLEND3 than that in CONT and BLEND1. The increased additive levels linearly decreased (p<0.05) erythrocytes, haemoglobin, and haematocrits values. At day 21, total triglyceride was lower (p<0.05) in BLEND3 than that in BLEND1 and BLEND2. The LDL level was lower (p<0.05) in BLEND3, whereas the HDL level was higher (p<0.05) in CONT than that in other groups. Creatinine was higher (p<0.05) in BLEND3 than in other groups. The ileal lactose negative Enterobacteriaceae counts were lower in BLEND1, BLEND2, and BLEND3 than in CONT (p<0.05). The duodenal villi height to crypt depth ratio (VH/CD ratio) was higher (p<0.05) in BLEND1 than that in CONT and BLEND2. In the ileum, the VH/CD ratio linearly increased (p<0.05) with the elevated additive levels. In conclusion, the combination of A. bilimbi fruit filtrate, wheat bran, and S. cerevisiae was beneficial in reducing intestinal pathogen load and improving intestinal morphology of broilers.